Evaluating SEVIMA Academic System Effectiveness in Managing Lecturer Performance Through the DeLone–McLean Information Success Model - Marumpe, Dody Pratama; Yulindisti, Elga; Hafiidz, Ziqri Muhamad; Rahmasari, Naila Ayu; Yosefin, Emelia (Yayasan Sinergi Kawula Muda, 2026)
Digital transformation has increased the demand for academic information systems that are accurate, user-friendly, and interoperable. At Universitas Tanjungpura, SEVIMA functions as a central reporting system for lecturer performance within a fragmented digital ecosystem that includes SISTER, Edlink, SKP, and SINTA. This fragmentation often leads to usability issues, unclear information, limited service responsiveness, and reduced work efficiency. This study aims to examine the effects of system quality, information quality, and service quality on system use, user satisfaction, and lecturer performance, as well as the mediating roles of system use and user satisfaction. A quantitative approach was employed by surveying 119 lecturers who actively use SEVIMA, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate moderate explanatory power, with R² values of 0.630 for user satisfaction, 0.582 for system use, and 0.618 for lecturer performance. All quality dimensions significantly influence system use and user satisfaction. User satisfaction exerts the strongest direct effect on lecturer performance, followed by system use. Mediation analysis confirms that both variables significantly mediate the relationship between quality dimensions and lecturer performance, with user satisfaction acting as the dominant mediator. These findings emphasize the importance of improving system integration, user-centered design, and institutional support to enhance lecturer performance and reduce digital fatigue in higher education information systems.